2020
DOI: 10.1111/jan.14699
|View full text |Cite
|
Sign up to set email alerts
|

Can foot reflexology be a complementary therapy for sleep disturbances? Evidence appraisal through a meta‐analysis of randomized controlled trials

Abstract: Aims To systematically summarize and quantify the effects of foot reflexology on improvements in sleep disturbances. Design Systematic review and meta‐analysis. Data sources Datasets including PubMed, Web of Science, Scopus, EMBASE, Cochrane Library, Google Scholar, CINAHL and two Chinese electronic databases (i.e., AiritiLibrary and China National Knowledge Infrastructure) were used to search from their inception to 31 January 2019. Review methods Studies which were randomized controlled trials that reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Receiving a certificate for participation in treatment sessions has also increased the child's motivation toward coping with insomnia and follow the principles of this protocol even after the end of treatment sessions. Therefore, the use of the The researchers concluded that reflexology or foot reflexology massage is effective in the improvement of insomnia in adults and the elderly (23,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receiving a certificate for participation in treatment sessions has also increased the child's motivation toward coping with insomnia and follow the principles of this protocol even after the end of treatment sessions. Therefore, the use of the The researchers concluded that reflexology or foot reflexology massage is effective in the improvement of insomnia in adults and the elderly (23,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a meta-analysis, Huang et al examined the effect of foot reflexology on adult sleep disturbances. The results of the aforementioned study showed that foot reflexology is a noninvasive and convenient intervention to alleviate sleep disturbances and improve the sleep quality of adults (23).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several meta-analyses on foot reflexology have been published [40][41][42][43][44] and showed the technique was an effective complementary therapy for treating functional constipation, relieving fatigue, improving sleep disturbance, and improving glycemic control and diabetic peripheral neuropathy. However, no meta-analysis has shown the effects of foot reflexology on vital signs.…”
Section: Similarities and Differences With Other Published Studiesmentioning
confidence: 99%
“…Additionally, it is accompanied by easy acceptance and cooperation between children and parents [ 15 ]. Among these methods, foot reflexology is a type of massage, which is one of the most important complementary therapies used among nurses [ 16 ]. Different studies have shown that reflexology improves the symptoms of appendectomy [ 17 ], and cancer pain [ 18 ], and some physiological symptoms in children [ 19 ].…”
Section: Introductionmentioning
confidence: 99%